Training as a Potent HRD Technique: An Opinion Survey of Stock Brokerage Firms - Vijayran, Manisha; Choudhary, Himanshu (Gyan Management Journal, 2009)
An opinion survey was conducted to see the attitude of employees on the various aspects of training viz, management's attitude, selection process, quality of training, impact on individuals, impact on productivity and post training assessment in different categories of stock brokerage companies in DelhiNCR. A sample of75 respondents from 5 stock brokerage companies namely Religare, Share khan, KarlYJ, Reliance Money, Emkay Share and Stock was taken. The findings suggest that by and large, most of the employees were satisfied with various aspects of training but their attitude differed due to the difference in their age, gender, designation, experience and educational background.
Keywords: Human Resource Development; Training; Attitude; Productivity and Post training assessment